Anal adenocarcinoma: Treatment outcomes and trends in a rare disease entity. (7th June 2019) - Wegner, Rodney E.; White, Richard J.; Hasan, Shaakir; Raj, Moses; Monga, Dulabh; Finley, Gene; Kirichenko, Alexander V.; McCormick, James
Abstract: Importance: Primary Adenocarcinoma of the anus is a rare disease with a poor prognosis and thus tends to have a more aggressive treatment algorithm, typically involving a surgical approach. Prior to 2001, a few retrospective studies outlined improved outcomes with the incorporation of surgery with chemoradiation. However, since the publication of these studies, advancement in radiotherapy modalities and imaging have left the question of improved outcomes while reserving surgery for salvage. Objective: We conducted this National Cancer Database (NCDB)‐driven retrospective study to analyze treatment trends and outcomes in the current time from 2004 to 2015 with respect to chemoradiation and surgery. Design: Retrospective NCDB tumor registry data review—using propensity score‐adjusted multivariable analyses for survival. Setting: Database review. Participants: We selected for patients listed in the NCDB with AJCC stage 1‐3 anal adenocarcinoma diagnosed between 2004 and 2015 and selected out patients with undocumented/stage 4 disease, those with radiation outside the pelvis, not treated with systemic therapy and patients lost to follow‐up. Exposure(s): None. Main outcomes and measures: Overall survival and use of surgery in the up‐front management of anal adenocarcinoma. Results: Of the 1729 patients eligible in this study, 1028 were treated with surgery as up‐front management and 701 had definitive chemoradiation. Median overall survival for all patients was 55 months with a 5‐year survival rate of 55%. Patients treated without surgery had worse overall survival, median survival of 45 months compared to 87 months ( P < 0.0001) with 5‐year survival rates of 42% and 55% in favor of incorporation of surgery. Analysis across patients treated with surgery alone, surgery followed by adjuvant chemoradiation, neoadjuvant chemoradiation followed by surgery, and chemoradiation alone had median survival rates of 78, 83, 92, and 46 months, respectively. Propensity score‐adjusted multivariable analysis identified older age, grade 3, high comorbidity score, and lack of surgery as predictive of worse outcome. Conclusions and Relevance: The results of the NCDB analysis indicate improved overall survival with the incorporation of surgery into the initial management of anal adenocarcinoma when compared to chemoradiation alone, despite the omission of surgery in up to 50% of the cases logged. Our results corroborate earlier studies published prior to the year 2000 for surgery to be included in the definitive management of anal adenocarcinoma. Abstract : This analysis used the National Cancer Database to look at treatment trends in the rare adenocarcinoma of the anal canal. Surprisingly, almost half of all cases were managed nonoperatively, with resultant inferior outcome compared to those patients who underwent surgery as part of their management.